Mathematical Modeling to Reduce Disordered Cell Division - Kuloğlu, Bahar (Darul Yasin Al Sys, 2025)
The Fibonacci sequence is a sequence of numbers that gets closer and closer to the golden ratio when divided by the number before it. The golden ratio has been recognized since antiquity as the order relation that gives the best harmony and proportions in many formations in art and nature. Fibonacci polynomials, which are obtained with the help of these number sequences, are a mathematical modelling developed to be used in many branches of science. The correlation data of the 3-step and 4-step Fibonacci polynomials obtained from the division accelerations of cells, which are standardly indexed to irregular division, and the development of Fibonacci polynomials were obtained. In this correlation, it is seen that the aggregation in the interval [0,1] is closer to 0 in the 3-step Fibonacci polynomial, while it moves away from 0 in the 4-step Fibonacci polynomial. The 4-step Fibonacci polynomial obtained here represents the division modelling of any cell indexed to irregular division. In order to ensure the digitizability of the obtained 3-step and 4-step Fibonacci polynomials, the coefficients of these polynomials are converted into a BINARY code system, then ENTROPI values are calculated by taking polynomials that can take values less than 1 in the interval [0,1] according to the definition of probability density functions and irregular division comparisons are made by obtaining scatter plots.